To the sun that heats more (Journal of Parents and Teachers, 2014)
Deified or “created by God”, object of artistic representation in monuments, painting, cinema, literature or music… the Sun has caused and still causes curiosity and therefore human beings study the Sun. It could be thought that a so close star cannot offer more surprises but this is far from reality. This article answers some questions such as what the Sun is made up of and why it shines, until where the Sun can reach and why it varies.
Keywords: astronomy; didactics; celestial body; sun; star